Ask the Experts: Pediatric Type 1 diabetes: adjunctive therapies, celiac disease and the role of the primary care physician. (November 2012) - Luca, Paola; Hamilton, Jill; Mahmud, Farid H; Usher-Smith, Juliet
Paola Luca is a clinical fellow in pediatric endocrinology and metabolism at The Hospital for Sick Children (ON, Canada). She obtained her medical degree at the University of Toronto (ON, Canada) and completed her training in pediatrics at The Hospital for Sick Children. She is currently pursuing a Master of Science through the Institute of Medicine at the University of Toronto. Her research focus is evaluating clinical outcomes of adolescents with severe obesity enrolled in the interdisciplinary weight management program at The Hospital for Sick Children. Jill Hamilton is a pediatric endocrinologist at The Hospital for Sick Children, Medical Director of the Sick Kids Team Obesity Management Program (STOMP), Senior Associate Scientist and Associate Professor of Pediatrics at the University of Toronto. Her clinical work is in endocrinology and diabetes, with a particular focus in the area of obesity. She completed her medical school training at the University of Ottawa (ON, Canada) and then trained at The Hospital for Sick Children in Toronto for pediatrics and endocrinology. Her research has focused on insulin resistance, pancreatic β-cell function and the metabolic complications of obesity in childhood. This has included evaluation of insulin resistance and completion of clinical trials using adjunctive therapies to improve metabolic control in children and adolescents with Type 1 diabetes. Farid H Mahmud received his university training at the University of Alberta Medical School (AB, Canada). He subsequently trained in pediatrics at the University of Alberta. FH Mahmud specialized in pediatric endocrinology at the Mayo Clinic in Rochester, MN, USA. He also completed specific Clinical Research Training from the Mayo Graduate School of Medicine. FH Mahmud is clinically active in diabetes and endocrinology, as well as specialized areas of pediatric calcium disorders and is involved in education through his activities as Assistant Professor at University of Toronto in undergraduate and postgraduate teaching. FH Mahmud's research interests include the study of conditions associated with Type 1 diabetes, such as celiac disease, and the evaluation of early atherosclerotic risk factors in young patients with endocrine conditions who are at high risk of cardiovascular disease, including both Type 1 and 2 diabetes, insulin resistance and obesity. In addition, FH Mahmud is an investigator in AdDIT and is also leading a longitudinal study evaluating the impact of celiac disease screening and treatment in children and young adults with Type 1 diabetes, as part of the JDRF–Canadian Clinical Trial Network. Juliet Usher-Smith is an academic clinical fellow in General Practice at the Primary Care Unit, Institute of Public Health, University of Cambridge (Cambridge, UK). She is funded by the National Institute for Health Research and her research focuses on the diagnosis of Type 1 diabetes in children. This has included systematic reviews of the factors associated with diabetic ketoacidosis at diagnosis and the variations between countries and current studies, funded by the Royal College of General Practitioners Scientific Foundation Board, exploring the pathway to diagnosis from the perspective of the child, family and general practitioner.